All-or-nothing cooperative self-assembly of an annulene sandwich. - Sprafke, J; Odell, B; Claridge, T; Anderson, H (2011)
Ring-fenced: A 14-component assembly is formed by coordinating 1,4-diazabicyclo[2.2.2]octane (DABCO) to a [12]porphyrin nanoring. The 24 zinc-nitrogen interactions in this sandwich complex lock each conjugated macrocycle into a planar conformation, dramatically sharpening the near-IR absorption band. This result highlights the scope of double-strand formation as a way of creating nano-objects with well-defined shapes. Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.